Caribbean Report 28-08-1995 - Goffe, Leslie (anchor); Holder, Claire (interviewee); Alert, Pat (interviewee); Roberts, Andy (interviewee); Condon, Paul, Sir (interviewee); Abbott, Diane (interviewee); Augustus, Patrick (interviewee); Christie, Merrick (interviewee); Christie, Linford (interviewee); Trant, William (interviewee) (The British Broadcasting Corporation, 1995)
In this special edition of BBC Caribbean Report, Leslie Goffe examines the recent headlines in Britain's Sunday Express newspaper which stated that there is a crisis over the melt-down of West Indian family life. The black ethnic group is the only one in which single mothers out-number married ones. Moreover, the Commissioner of London Police Force, Sir Paul Condon made a controversial statement which linked race and crime in the capital. Condon stated that a small number of black youngsters seem to be committing a large number of the robberies in London. In Britain, African-Caribbean men are the single most vulnerable group. British Olympic and world champion sprinter, Linford Christie, is not a winner in the eyes of his son Merrick who denounced his father in the British media. Several British newspapers have used Linford Christie's family to highlight the current debate about single parents. William Trant, Director of Britain's West Indian Standing Conference comments that running away from responsibilities of all kinds has become a way of life for black youngsters in Britain.
1. Introduction by Leslie Goffe (00:00-00:28)
2. Is Britain's Caribbean community in melt-down (00:29-15:15)
Keywords: Blacks -- Great Britain -- Social conditions; West Indians -- Great Britain; Single-parent families -- Great Britain; Families, Black -- Great Britain; Family crises -- Great Britain; Single parents -- Great Britain; Fathers -- Family relationships; Absentee fathers -- Great Britain; Young men -- Great Britain -- Social conditions; Single mothers -- Great Britain; Crime and race -- Great Britain; Great Britain -- Race relations